Manajemen Parenting dalam Penguatan Pendidikan Karakter Religius Anak - Indi Aunullah (EDUCARE: Jurnal Ilmu Pendidikan, 2022)
This study seeks to study the strengthening of religious character education in children in school with parenting management to regulate and control child habituation when at home. This research uses a descriptive qualitative approach of this type of case study. The location of the search is MTs Al-Muddakir Banjarmasin City. Data analysis techniques in the form of data reduction, data display, and data verification or conclusions. The results showed that; First, the institution MTs Al-Muddakir strengthens planning in coordination with the parents of students, second, the management of religious character is carried out by religious habituation, time management, and also follow-up progress. The implications obtained in strengthening religious character education in coordination with parents are able to instill religious character for the children with habituation carried out.